Detecting Subtle Shifts: Comparing SME Performance Drivers Pre and During the Covid-19 Pandemic - Soza Sydney Simango; Helper Zhou (African Journal of Inter-Multidisciplinary Studies)
Small and Medium Enterprises (SMEs), especially those in the South African tourism sector, were significantly impacted by the Covid-19 pandemic. Many experienced a decline in performance due to decreased consumer demand resulting from travel restrictions. Understanding these enterprises’ performance pre and post the pandemic will provide insights into how enterprise development practitioners and policy makers could best respond to crises such as this. The study harnessed the Resource-Based View theory to unveil subtle shifts in SMEs’ performance drivers due to the impact of the pandemic. This is important as pre-Covid-19, tourism SMEs with sufficient resources and capabilities were likely to enjoy a competitive advantage and better performance than those lacking such. However, the pandemic disrupted many of these resources and capabilities as travel restrictions and decreased demand made it difficult for SMEs to maintain their customer base or invest in new markets. The Difference in Difference (DID) technique was employed due to its ability to isolate the impact of the pandemic on firm performance by comparing pre- and post-Covid-19 features. As expected, the results showed that the pandemic negatively impacted South African tourism SMEs. This was evident in decreased total asset value, sales volumes, revenue and the number of product offerings. Surprisingly, it was found that having a business plan in place negatively impacted performance before Covid-19. However, post-pandemic, business planning was a crucial positive driver of SME performance. Company age negatively impacted performance post the pandemic, indicating organisational rigidities among tourism SMEs during crises. Despite being home to the popular Garden Route, the Western Cape province suffered more negative effects than other provinces. Lastly, entrepreneur experience and business incubation positively impacted SME performance during the pandemic. Based on these findings, it is recommended that key stakeholders take the evolving performance drivers in the SME sector into account in order to craft support measures that lead to increased, sustainable business performance.